2016
DOI: 10.1590/1413-81232015214.13722015
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre consumo alimentar, atividade física, fatores socioeconômicos e percentual de gordura corporal em escolares

Abstract: (RP = 0,61; IC: 0,79

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
18
1
1
Order By: Relevance
“…identified a concomitant increase in physical activity and fat percentage. However, in contrast with the present study, some research did not identify an association between these variables 24 25 These divergences may be due to several demotivating circumstances for adolescent students with excess body fat to adopt the practice of physical activity.…”
Section: Discussioncontrasting
confidence: 99%
“…identified a concomitant increase in physical activity and fat percentage. However, in contrast with the present study, some research did not identify an association between these variables 24 25 These divergences may be due to several demotivating circumstances for adolescent students with excess body fat to adopt the practice of physical activity.…”
Section: Discussioncontrasting
confidence: 99%
“…So that, adolescents, realising they were overweight, could be limiting their intake to the foods in this pattern, which are known to be unhealthy and potentially obesogenic. A further reason to believe this finding is due to reverse causality is that an inverse association between unhealthy dietary intake and body fat percentage was found in another study based on the same sample [35]. Alternatively, longitudinal studies may be performed in order to avoid reverse causality.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, aiming to partially correct possible bias caused by refusal or loss of subjects, the percent differences between the respondents and the eligible population was also considered in the calculation of the sampling weight. Furthermore, it has been reported that studies involving adolescents have lower adherence rates than those observed with other age groups [16]. Moreover, measuring the contribution of engagement in physical activity using a self-administered questionnaire is a limitation of this study.…”
Section: Discussionmentioning
confidence: 80%
“…This is a cross-sectional school-based study linked to a research project financially supported by the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq, National Council for Scientific and Technological Development) -Case nº483955/2011-6-carried out from September 2012 to June 2013 in the city of Florianópolis, Santa Catarina, Southern Brazil. The procedures for calculation of sample size sampling, and data collection and analysis have been described in a previous study [16]. A probabilistic sample of students aged 11-14 years enrolled in public (municipal, state, and federal) and private middle and high schools in Florianópolis was used.…”
Section: E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation